Comparison among the Atherogenic Index of Plasma, Ratios of Lipoproteins, Apolipoproteins and Cholesterol Retention Factor (CRF) inPatients with Metabolic Syndrome - Khan, Sikandar Hayat; Afzal, Ahmed Hayat; Gilani, Mehreen; Akhtar, Faisal Naveed; Shahid, Rahat (Pakistan Armed Forces Medical Journal, 2023)
Objective: To evaluate various lipid, lipoprotein and apolipoprotein ratios among participants with and without metabolic syndrome.Study Design: Comparative cross-sectional study.Place and Duration of Study: Naval Hospital, Islamabad Pakistan, from Jan 2019 to Dec 2020.Methodology: We selected 164 patients with metabolic syndrome. Metabolic syndrome was diagnosed as per “NCEP-defined metabolic syndrome criteria”. Insulin resistance was calculated using Homeostasis Model Assessment for Insulin Resistance (HOMA-IR). Various apolipoproteins were calculated using the turbidimetric method on Humastar-200 and lipoproteins by direct detergent methods.Results: The differences for Apo-B/Apo-A1 were found to be higher among metabolic syndrome subjects [{Metabolic syndrome (n=83):0.55±0.22} vs {Non-Metabolic syndrome (n=81):0.50±0.29}, p=0.271]. Area Under Curve (AUC) was highest for the atherogenic index of plasma [0.744], followed by both total cholesterol/HDLc [0.641], Cholesterol Retention Factor (CRF) having [0.641], Apo-B/Apo-A1[0.593] and HDLc/LDLc [0.418].Conclusion: Differences between subjects with and without NCEP-defined metabolic syndrome were significant for the atherogenic index of plasma (AIP), HDLc/LDLc, and Cholesterol Retention Factor (CRF).